Health Education in Pandemic: Students’ Perception and Motivation Correlate with Prevention Behaviors - Rosa Susanti; Ilmi Zajuli Ichsan; Nina Sri; Rita Istiana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The prevention of Coronavirus Disease 2019 (Covid-19) is everyone’s effort everywhere including in health education. University is one of the most vulnerable places for Covid-19 transmission. Students, as one of the community components in the university, have a vital role in preventing the spread of Covid-19 with appropriate perception and motivation. The research aims to identify the correlation between perception, motivation, and efforts of preventing Covid-19 transmission to students of the Faculty of Health. The research method is descriptive with surveys as the data collection technique. Instruments used in the research are in the form of instruments of perception, motivation, and behavior that are developed with 10 items each. The research results indicate a significant relationship between perception, motivation, and behavior of Covid-19 prevention. Several items with the lowest average score are the first item for perception (4.05), the ninth item for motivation (4.06), and the fifth item related to preventive behaviors (4.14). Efforts in improving the behavior of Covid-19 prevention can be carried out through the enhancement of education at the university level. The research concludes that there is a relationship between the perception, motivation, and behavior of students of the Faculty of Health in preventing Covid-19 transmission. Keywords: Prevention Behaviors, Health Education, Preventing Covid-19